CORRELATION STUDY BETWEEN THREE DIFFERENT GENES EXPRESSION AND CHRONIC MYELOID LEUKEMIA IN IRAQ - & Altaee, Aljoubory (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The following study was conducted to investigate the correlation between the expression of three different genes (NOB1, DDX47, CD101 (with the occurrence and development of chronic myeloid leukemia (CML) in Iraq. The difference in the expression of these genes between patients and healthy controls was studied. Moreover the correlation of age and gender with CML occurrence and comparing with control was also examined. Results showed significant increases in mean of gene expression level (ΔCt) of patient groups for all genes compared to the corresponding ΔCt means in control group, also the gene expression folding (2-∆∆Ct) reflect significant differences in the expression of these genes and CD101, mRNA showed the highest level in CML patients which reached to (3.44), while NOB1 and DDX47 recorded (2.90 and 1.08) respectively. On the other hand no significant differences were recorded according to age and gender between CML patients and control, CML disease could affect any age and both male and female.